2019
DOI: 10.1021/acs.jchemed.8b00802
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Peer-Focused Recitation To Enhance Student Success in General Chemistry

Abstract: This study investigates the impact of peer-focused, active-learning recitation sessions with the large-enrollment sections of General Chemistry I courses at Mississippi State University (MSState). Over a period of four semesters beginning in Spring 2016, recitation sessions were implemented into the General Chemistry I (CH1213) courses at MSState. In order to assess the influence of the active learning instructional hour, we studied departmental final (standardized ACS) exam scores, pass/fail rates for the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…3 Groups of three were chosen because previous studies have shown that larger groups do not allow for all members to fully participate in the problem-solving process. 6,7 The students worked in these groups independently, but both the TA and undergraduate peer facilitator would circulate the room to provide guidance when needed and ask questions to probe understanding. There was no significant change in discussion attendance after the transition to online learning (Figure 3A).…”
Section: Discussion Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Groups of three were chosen because previous studies have shown that larger groups do not allow for all members to fully participate in the problem-solving process. 6,7 The students worked in these groups independently, but both the TA and undergraduate peer facilitator would circulate the room to provide guidance when needed and ask questions to probe understanding. There was no significant change in discussion attendance after the transition to online learning (Figure 3A).…”
Section: Discussion Sectionsmentioning
confidence: 99%
“…Additionally, because studies have shown that peer-oriented learning enhances retention and understanding, the students were randomly split into groups of no more than three that were encouraged to collaborate on answering the questions on the worksheets . Groups of three were chosen because previous studies have shown that larger groups do not allow for all members to fully participate in the problem-solving process. , The students worked in these groups independently, but both the TA and undergraduate peer facilitator would circulate the room to provide guidance when needed and ask questions to probe understanding. There was no significant change in discussion attendance after the transition to online learning (Figure A).…”
Section: Class Structurementioning
confidence: 99%
“…Although social presence theory has not been researched extensively in the context of online chemistry learning, chemical educational research found a significant effect of the role of peer in students' chemistry learning outcome [12][13][14][15][16] in regular, in-person classrooms. For example, in a classroom study examining students in a general chemistry course, when students were asked to discuss concepts learned in class with another student, their chemistry exam scores were significantly higher (i.e., 17.76 percentile points higher) than students who only received traditional lecture-based teaching [12]. Similarly, in another study, learning chemistry with a peer leader was found to result in better critical thinking than a traditional lecture-based approach [13].…”
Section: The Role Of Peer In Chemistry Learning: Social Presence Theorymentioning
confidence: 99%
“…Near-peer facilitators are selected based on success in the course that they will be working within; although not a requirement, many peer instructors have experienced peer-supported pedagogies in the course for which they are assisting. Near-peers guide students through individual and small group activities ranging from single classroom-response system questions (e.g., clicker questions), to back-of-the-chapter textbook problems, to multi-question guided learning worksheets (e.g., Tien, Roth, & Kampmeier, 2002;Michael, 2006;Arendale, 2010;Salomone & Kling, 2017;Freeman et al, 2014;Perera, Wei, & Mlsna, 2019). While peer instructors often answer questions, the goal of a near-peer is to 'facilitate' learning; therefore, they often respond to student questions with a different question to help guide students to their own answer (Wilson & Varma-Nelson, 2016;Tenney & Houck, 2003;Drane, Smith, Light, Pinto, & Stewart, 2005;Tien, Roth, & Kampmeier, 2002;Arendale, 2010;Salomone & Kling, 2017;Freeman et al, 2014;Perera, Wei, & Mlsna, 2019).…”
Section: Peer-led Team Learning and Leaning Assistant Pedagogiesmentioning
confidence: 99%
“…Near-peers guide students through individual and small group activities ranging from single classroom-response system questions (e.g., clicker questions), to back-of-the-chapter textbook problems, to multi-question guided learning worksheets (e.g., Tien, Roth, & Kampmeier, 2002;Michael, 2006;Arendale, 2010;Salomone & Kling, 2017;Freeman et al, 2014;Perera, Wei, & Mlsna, 2019). While peer instructors often answer questions, the goal of a near-peer is to 'facilitate' learning; therefore, they often respond to student questions with a different question to help guide students to their own answer (Wilson & Varma-Nelson, 2016;Tenney & Houck, 2003;Drane, Smith, Light, Pinto, & Stewart, 2005;Tien, Roth, & Kampmeier, 2002;Arendale, 2010;Salomone & Kling, 2017;Freeman et al, 2014;Perera, Wei, & Mlsna, 2019). Learning facilitation, in this way, requires confidence in facilitating learning as well as a belief that collaborative learning is an effective pedagogy.…”
Section: Peer-led Team Learning and Leaning Assistant Pedagogiesmentioning
confidence: 99%